Teledermatology: Impact of a Computer Management Tool in Remote Areas of Chile [Teledermatología: Impacto de Una Herramienta de Gestión Informática Para Zonas Remotas de Chile] - Fuenzalida-Cruz, H; Loubies-Muñoz, R; Toso-Diaz de la Vega, S (Ediciones Doyma, S.L., 2017)
Introduction Chile is a country of more than 4200 km long located in South America. It has 2-mountain ranges (Costa and Andes mountain ranges) that run parallel through the entire country. It also has numerous archipelagos, channels, fjords, more than 2000 islets, and more than 3700 islands. Numerous areas of the country are difficult to reach, and are fairly isolated. The low availability and increased demand for specialist care, the difficulty and transport cost for patients resident in remote areas has meant that there is an important gap in the possibility of appropriate and quality care of their population. In this context, telemedicine, based on the application of technology and communications, has been used to bring the professionals and equipment closer in order to meet the demands of dermatological care. Methodology Data obtained from teledermatology in a period of 20 months, from September 1st of 2014 to May 1st of 2016, were analyzed. In which a total of 1764 consultations derived from the Reloncavı Health Service were evaluated by dermatologists from the Dermatology Service of El Pino Hospital in Santiago de Chile. Results The analysis of the Teledermatology of the patients referred shows that most of the patients are women, and between 16 and 45 years old. More than a half of the patients were advised to continue their medical checks in the Primary Care System. Furthermore, there was more than a 60% agreement in the diagnoses made by general practitioners and specialists. Conclusion With this system, we were able to decrease the waiting time of patients seeking dermatological care. It was possible to educate the medical staff working in this isolated places, providing them with tools to improve their skills. In addition, we were able to give priority to those patients with malignant or complex diseases. Therefore, this system is cost-beneficial and represents a huge social improvement. © 2017 Elsevier España, S.L.U.